Factors Associated With Initiation of Extracorporeal Cardiopulmonary Resuscitation in the Pediatric Population: An International Survey. Issue 3 (1st June 2021) - Nguyen, Duy-Anh; De Mul, Aurélie; Hoskote, Aparna U.; Cogo, Paola; da Cruz, Eduardo M.; Erickson, Simon; Lasa, Javier J.; Thiagarajan, Ravi R.; Bembea, Melania M.; Karam, Oliver; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Although extracorporeal cardiopulmonary resuscitation (ECPR) is increasingly utilized in the pediatric critical care environment, our understanding regarding pediatric candidacy for ECPR remains unknown. Our objective is to explore current practice and indications for pediatric ECPR. Scenario-based, self-administered, online survey, evaluating clinical determinants that may impact pediatric ECPR initiation with respect to four scenarios: postoperative cardiac surgery, cardiac failure secondary to myocarditis, septic shock, and chronic respiratory failure in a former preterm child. Responders are pediatric critical care physicians from four societies. 249 physicians, mostly from North America, answered the survey. In cardiac scenarios, 40% of the responders would initiate ECPR, irrespective of CPR duration, compared with less than 20% in noncardiac scenarios. Nearly 33% of responders would consider ECPR if CPR duration was less than 60 minutes in noncardiac scenarios. Factors strongly decreasing the likelihood to initiate ECPR were out-of-hospital unwitnessed cardiac arrest and blood pH <6.60. Additional factors reducing this likelihood were multiple organ failure, pre-existing neurologic delay, >10 doses of adrenaline, poor CPR quality, and lactate >18 mmol/l. Pediatric intensive care unit location for cardiac arrest, good CPR quality, 24/7 in-house extracorporeal membrane oxygenation (ECMO) team moderately increase the likelihood of initiating ECPR. This international survey of pediatric ECPR initiation practices reveals significant differences regarding ECPR candidacy based on patient category, location of arrest, duration of CPR, witness status, and last blood pH. Further research identifying prognostic factors measurable before ECMO initiation should help define the optimal ECPR initiation strategy.